An alternative CTCF isoform antagonizes canonical CTCF occupancy and changes chromatin architecture to promote apoptosis - Jiao Li; Kaimeng Huang; Gongcheng Hu; Isaac A. Babarinde; Yaoyi Li; Xiaotao Dong; Yu-Sheng Chen; Liping Shang; Wenjing Guo; Junwei Wang; Zhaoming Chen; Andrew P. Hutchins; et al. (Nature Communications, 2019)
CTCF plays key roles in gene regulation, chromatin insulation and organizing the higher-order chromatin architecture of mammalian genomes. Here the authors investigate the function an alternatively spliced shorter CTCF isoform, finding that this isoform antagonizes canonical CTCF occupancy and changes chromatin architecture to promote apoptosis.